O mundo imaginado, mas nem tanto, de Carmo Bernardes - Araújo, Miryam Moreira Mastrella de (2009)
As a cultural event, literature is also a form of knowledge of social life; if it doesn't provide us with answers, it may, however, enlarge the field of social research, making it possible for some issues to emerge as they're seen in a particular group at a given moment. This study intends to discuss the emergency of certain social issues as they appear in two works by the writer from Minas Gerais-Goiás, Carmo Bernardes: Perpetinha: um drama nos babaçuais (1991) and Santa Rita (1995). We intend to verify how some aspects of reality are transfigured in both works, such as relations between men and women, and others. From the way literature shapes these issues, we want to examine how they are treated by social theory (sociology, anthropology and historiography). The sertão, in the two novels, appears as a place of counter-hegemonic speech, because it is not restricted to a display of signs, that is, mere descriptions of customs, landscapes and human types who would be at risk of disappearing due to the area's insertion process to the capitalist logic, i.e., because of the materiality loss the sertão has undergone over the last decades. These descriptions serve as background, as scene for the development of other themes, such as inequalities, injustices, prejudice and oppression of workers.